Navigating knowledge management systems in Indonesian Financial Institutions: a systematic literature - Sinaga, Nicky Yasmidar Salim; Rahmi, Rahmi (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Financial institutions employ sophisticated knowledge management systems to disseminate company information, aligning with their organizational objectives, vision, and mission. The present research seeks to elucidate the archetype of the knowledge management system deployed, its consequential impacts, and the potential impediments encountered during its operational phase. The empirical data was sourced from many scholarly articles centered on knowledge management systems within financial institutions. A systematic literature review (SLR) approach underpins the methodology of this study. The survey data were descriptively analyzed using population, comparison, outcomes, and context (PICOC) parameters. An analysis of seven pertinent articles identified five distinct knowledge management system archetypes, their respective influences on the organizations, and five principal challenges that obstructed seamless implementation. Based on the findings, the meticulous review of scholarly articles centered on adopting knowledge management systems within financial services enterprises has illuminated the existence of five distinct knowledge management system paradigms. Each model is intricately woven into the institutions’ organizational structure and cultural ethos.